Psychic defense in the first Freudian topography: why are drives repressed? - Sanches, Aline; Bocchi, Josiane Cristina [UNESP] (FapUNIFESP (SciELO), 2021)
Since the beginning of Freudian theorization, inhibition, defense and censorship are processes that must affect the instincts. The primitive drives needs to be repressed or transformed. This article proposes to discuss the articulation between sexual drives and psychic defense, throughout the pre-psychoanalytic period and the first drive theory. We situate the conflict between sexuality and repression, pointed out by Freud as characteristic of psychoneurosis, whereas in actual neurosis, anxiety is related to a quantitative dimension and not exactly to a psychic conflict. In this case, disagreements between a corporeal sexual and its psychic representation are revealed. It is intended, in this work, to highlight the negative character of the drives and to elucidate the nature of the antagonism that opposes the sexual drives. The formulation of the self-preservation drives, as what must be opposed to the sexual drives, does not completely explain why it is imperative that something happens against the fundamental drive experiences. Satisfaction of drives in the raw state causes damages, both psychically and socially; therefore, the repression of sexual drives is a necessary condition for individual and collective existence. Thus, something specific of the human is evidenced: if all nature works affirming the instinct, the human species only develops from its negation. Based on such theoretical constructions, it is questioned whether psychoanalysis still remains too dependent on a conception of nature covered with moral presuppositions, supporting the notion that the nature has to be continually denied, removed, coerced and domesticated, in favor of social constructions quite questionable but accepted as necessary.
Defesa psíquica na primeira tópica freudiana: por que as pulsões são reprimidas?
Keywords: Instincts; Repression; Sexuality